Relative silence [large type] - Parks, Carrie Stuart (Thorndike Press large print Christian fiction series., 2020)
"A powerful family with dark secrets. After personal tragedy, Piper Boone retreats to her childhood home - a secluded mansion for the wealthy Boone family, who are practically American royalty. When catastrophe strikes, her family is put in the spotlight, and the line between victim and suspect gets blurred. A forensic artist with his own haunted past, Tucker Landry is drawn to Piper in the midst of the trauma, but the connections being made to her family might prove to be their undoing. With a hurricane beating down on the private island, there isn't much time to find answers. The truth will determine whether Piper lives or dies." -- Back cover.